A limit theorem for copulas - Alexander M. Lindner; Alexander Szimayer (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2005)
We characterize convergence of a sequence of d-dimensional random vectors by convergence of the one-dimensional margins and of the copula. The result is applied to the approximation of portofolio modelled by t-copulas with large degrees of freedom, and to the convergence of certain dependence measures of bivariate distributions.
urn:nbn:de:bvb:19-epub-1802-0
Keywords: 519; convergence; copula; t-copula